Worker and Public Health and Safety Current Views - Lal, Sara; Penzel, Thomas; Simpson, Ann (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book on "Worker and Public Health and Safety: Current Views" brings together current scholarly work and opinions in the form of original papers and reviews related to this field of study. It provides important and recent scientific reading as well as topical medical and occupational information and research in areas of immediate relevance, such as chronic and occupational diseases, worker safety and performance, job strain, workload, injuries, accident and errors, risks and management, fitness, burnout, psychological and mental disorders including stress, therapy, job satisfaction, musculoskeletal symptoms and pain, socio-economic factors, dust pollution, pesticides, noise, pathogens, and related areas.